Working Sessions as Public Relations Technique. A Case Study - Huaripata Yizuka, Cindy (2014)
The main objective of this research was to determine the influence of the organization of work sessions as a technique of PR on the clients’ image of a company. This technique enables organizations to approach their target public in order to communicate about theirs products, services, activities and behavior. It is expected to obtain placement, identification and also, to strengthen relation and communication with the public.Precisely, this explanatory research carried out in two groups (control and experimental) demonstrated that the organization of the work sessions in deed has influence on the image of the clients of a company. According to the results, it is stated that there is a 96.7% level of correlation between both variables.